Development of a Digital Platform: A Perspective to Advance Space Telepharmacy - Marlise A dos Santos; Juliana Herbert; Ilaria Cinelli; Jose Antonio L Burmann; Vinicius V Soares; Thais Russomano (IEEE Open Journal of Engineering in Medicine and Biology)
Goal: Lessons learned from decades of human spaceflight have helped advance the delivery of healthcare in rural and remote areas of the globe. Inclusion of the public in spaceflights is not yet accompanied by technology capable of monitoring their physical and mental health, managing clinical conditions, and rapidly identifying medical emergencies. Telepharmacy is a practice prioritizing pharmacotherapeutic guidance and monitoring to help improve patient quality of life, and can potentially expand the field of space medicine. We seek to advance pharmaceutical care through telepharmacy by developing a digital platform. Objective: This study focuses on the development of a digital platform for teleassistance and pharmaceutical teleconsulting services that builds on lessons learned in delivering space medicine. Methods: The platform contains evidence-based information on various drugs grouped by medical specialty, and also records and saves patient appointments. It has specific service protocols for service standardization, including artificial intelligence, to allow agility in services and escalation. All data is protected by privacy and professional ethics guidelines. Results: The telepharmacy platform is ready and currently undergoing testing for ground applications through validation studies in hospitals or medical clinics. Conclusions: Although developed for use on Earth, this telepharmacy platform provides a good example of how terrestrial healthcare knowledge and technology can be transferred to space missions.